2022
DOI: 10.3390/ph15081008
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Phytochemicals against Aluminum Chloride-Induced Alzheimer’s Disease through ApoE4/LRP1, Wnt3/β-Catenin/GSK3β, and TLR4/NLRP3 Pathways with Physical and Mental Activities in a Rat Model

Abstract: Background: Alzheimer’s disease (AD) is a neurodegenerative disorder that is associated with abnormal cognition. AD is aided in its initiation and progression by hereditary and environmental factors. Aluminum (Al) is a neurotoxic agent that causes oxidative stress, which is linked to AD progression. Additionally, Nrf2/HO-1, APOE4/LRP1, Wnt3/β-catenin, and TLR4/NLRP3 are the main signaling pathways involved in AD pathogenesis. Several phytochemicals are promising options in delaying AD evolution. Objectives: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 92 publications
2
33
0
Order By: Relevance
“…Aluminum is a neurotoxic agent that causes oxidative stress ( 7 ). It is known to cause toxic effects on various systems, including the brain, bone, Kidney, and blood ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum is a neurotoxic agent that causes oxidative stress ( 7 ). It is known to cause toxic effects on various systems, including the brain, bone, Kidney, and blood ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurodegenerative disease progression has been extensively shown to be influenced by oxidative stress, inflammation, and apoptosis (Behl et al, 2021;Merelli et al, 2021;Zarneshan et al, 2022). In this regard, previous studies indicated that Al exposure can induce various neurological disorders (Aly et al, 2011;Hamdan et al, 2022;Turkez et al, 2022). Therefore, chronic exposure to Al in mouse models has frequently been used as an experimental model of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Suppressed cholinergic transmission was reported to activate the inflammatory system by increasing N-methyl-D-aspartate receptor expression, disrupting cognition, and increasing neurotoxicity ( Haider et al, 2020 ; Amanzadeh Jajin et al, 2021 ; Firdaus et al, 2022 ). AlCl3 may cause neurodegeneration through multiple interlocking pathogenic pathways ( Wang et al, 2019 ; Shunan et al, 2021 ; Hamdan et al, 2022 ). However, one of the reasons that IMP is effective against Al-induced neurotoxicity is probably due to its anti-inflammatory action on cytokines and its role in normalizing ACh levels in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these premises, Hamdan et al [ 26 ] carried out a study on the neuroprotective activity of some phytochemicals such as morin, thymol, and thymoquinone in the absence/presence of physical and mental activities in a rat model of AD induced by aluminum chloride (AlCl 3 ). AlCl 3 led to a decline in spatial learning and memory, inducing histopathological changes in rat brains.…”
mentioning
confidence: 99%